Hi Im new to fourier transforms and need to know how to put the following into seperate parts

f(t) = e^-2t U(t-3)

f(t) = e^-t U(t-6)

Printable View

- May 22nd 2011, 12:13 AMhunterage2000Fourier Transforms question
Hi Im new to fourier transforms and need to know how to put the following into seperate parts

f(t) = e^-2t U(t-3)

f(t) = e^-t U(t-6) - May 22nd 2011, 12:28 AMmr fantastic
- May 22nd 2011, 12:40 AMhunterage2000
yeah thats the step function. I know the fourier transform definition formula but completely struggle with the maths of it.

Will f(t) = e^-2t U(t-3) be f(t) = 3, t < 0 e^-2t, t > 0 - May 22nd 2011, 05:57 AMCaptainBlack
- May 22nd 2011, 06:02 AMhunterage2000
I mean the seperate parts of the graph as in

f(t) = 3, t > 0

e^-2t, t < 0

I dont know how to take f(t) = e^-2t U(t-3) and put it in the above form. - May 22nd 2011, 12:21 PMmr fantastic
You are

**expected**to know that the Heaviside Step Function U(t - a) = 1 if t > a and zero if t < a. That is why I asked in my first post!

If you don't know the definition, then at this level you are**expected**to find a reference that explains it. I would be very very surprised if your textbook or class notes did not define it.

And if you know that U(t) = 1 for t > 0 and 0 for t < 0 then you are**expected**to understand the effect of a transformation such as U(t) --> U(t - a).